A new characterization of Chevalley groups $G_2(3^n)$ by the order of the group and the number of elements with the same order - Behnam Ebrahimzadeh; Hamid Shahbandarzadeh (AUT Journal of Mathematics and Computing)
In this paper, we prove that Chevalley groups $G_2(q)$, where $q=3^n$ and $q^2+q+1$ is a prime number, can be uniquely determined by the order of group and the number of elements with the same order.